2014
DOI: 10.1186/1471-2164-15-669
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study combined with biological context can reveal more disease-related SNPs altering microRNA target seed sites

Abstract: BackgroundEmerging studies demonstrate that single nucleotide polymorphisms (SNPs) resided in the microRNA recognition element seed sites (MRESSs) in 3′UTR of mRNAs are putative biomarkers for human diseases and cancers. However, exhaustively experimental validation for the causality of MRESS SNPs is impractical. Therefore bioinformatics have been introduced to predict causal MRESS SNPs. Genome-wide association study (GWAS) provides a way to detect susceptibility of millions of SNPs simultaneously by taking li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Previous findings showed that human miRNAs with single-nucleotide polymorphisms (SNPs) can be targets of genetic variation in human genomic DNA sequences and may be related to susceptibility of human disease ( 20 ). miRNA SNPs have inter-individual differences in disease diagnosis, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings showed that human miRNAs with single-nucleotide polymorphisms (SNPs) can be targets of genetic variation in human genomic DNA sequences and may be related to susceptibility of human disease ( 20 ). miRNA SNPs have inter-individual differences in disease diagnosis, treatment, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In a study aiming to search the SNPs resided in the miRNA recognition element seed sites (MRESSs) in several GWAS datasets, it was proposed that rs1053005 and rs1053023 polymorphisms affect the function of miR-4793 and miR-4506/4640, respectively. 27 In Figure 1, we summarized the effects of these polymorphisms on the function of potential predicted miRNAs, leading to upregulation of STAT3 and finally SLE pathogenesis via increased inflammatory cytokines and autoantibody production.…”
Section: Discussionmentioning
confidence: 99%
“…These two common polymorphisms have been suggested to affect the thermodynamic features and secondary structure of STAT3 3 0 -UTR and consequently the miRNA binding capacity of multiple miRNAs. 27,28 These polymorphisms can finally influence the expression of STAT3 and modulate the risk of SLE development. In the current study, we aimed to assess the plausible association between rs1053005 and rs1053023 and the susceptibility to SLE disease in the Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs achieve their biological function by binding to mature mRNAs and in most cases, decreasing the expression level of target mRNAs (26). The association between microRNA and human disease can be converted into an association between microRNA-mRNA interaction and human disease, thereby providing a means to influence microRNA-regulated human diseases (27). There is accumulating evidence indicating a significant miRNA contribution to depression, anxiety, and antidepressant action (28,29).…”
Section: Discussionmentioning
confidence: 99%